Slavic Borrowings in 20th-Century German Military Slang - Kułacz, Sławomir (Papers in Linguistics, 2025)
The article attempts to provide an overview of the influence of Slavic languages on German military slang during the key periods of the 20th century – namely, 1914–1918 and 1939–1990. This is done against a historical and social background, however, only the most significant factors are to be presented. So far, this issue has been signalled in the Polish language literature on linguistics, while in the German language literature it has only been discussed briefly and solely in relation to Russian influences. This article is based on German publications (mostly dictionaries) recording military slang. They have been rarely referenced in linguistic studies so far. The overview indicates that a significant portion of Slavicisms consists of proper names, which often underwent appellativization, or became part of hybrid compounds. Slavicisms were not only names referring to Eastern war reality but also dysphemisms, such as ironic names for Russian soldiers. Many Slavicisms had a humorous or even vulgar character. The group of over eighty examples presented in the article illustrates the main tendencies resulting from historical changes, such as the dominance of Russianisms in the post-war period and the emergence of previously absent vocabulary naming weapons and military equipment.